National–Global Upheavals are Destabilizing Higher Education - Marginson, Simon (International Higher Education, 2025)
<h3 id="amid-growing-nativism-and-migration-resistance-in-western-politics-coupled-with-geopolitical-conflict-between-the-united-states-and-china-the-local-and-national-identities-of-anglophone-and-european-higher-education-institutions-are-increasingly-in-tension-with-their-global-activity-and-commitment-to-cross-border-cooperation-based-on-academic-freedom" data-pm-slice="1 1 []">Amid growing nativism and migration resistance in Western politics, coupled with geopolitical conflict between the United States and China, the local and national identities of Anglophone and European higher education institutions are increasingly in tension with their global activity and commitment to cross-border cooperation based on academic freedom.